Photocatalytic adsorption bifunctional material based on mordenite as well as preparation method and application of photocatalytic adsorption bifunctional material

By forming a composite photocatalytic material of CdS/ZnS nanoparticles and g-C3N4 nanosheets on mordenite, the shortcomings of existing photocatalytic adsorbents in adsorption and photocatalytic activity are solved, efficient adsorption and recovery of heavy metal ions are achieved, and the stability and photocatalytic activity of the material are improved.

CN119524823APending Publication Date: 2025-02-28XIJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411550401.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing photocatalytic adsorbents have problems such as few surfactant sites, insufficient adsorption capacity, poor stability and high cost in the fields of environmental governance and energy conversion, making it difficult to effectively treat heavy metal-containing wastewater.

Method used

A mordenite-based dual-functional material is used to prepare mordenite MOR through a one-step hydrothermal crystallization process, and CdS/ZnS nanoparticles and g-C3N4 nanosheets are formed on its surface to form a composite photocatalytic material to improve adsorption and photocatalytic activity.

Benefits of technology

It realizes efficient adsorption and recovery of heavy metal ions, while improving the photocatalytic activity and stability of the material, reducing the preparation cost, and is suitable for sewage treatment and soil restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524823A_ABST
    Figure CN119524823A_ABST
Patent Text Reader

Abstract

The invention discloses a photocatalytic adsorption bifunctional material based on mordenite and a preparation method and application thereof.The preparation method comprises the steps that zinc chloride and cadmium chloride solutions and MOR are mixed, the MOR has electrostatic affinity and adsorption performance, Zn < 2 + > and Cd < 2 + > in waste water are removed, meanwhile, the ions are gathered around the MOR, after drying, the MOR adsorbing Zn < 2 + > and Cd < 2 + > is obtained, and the MOR adsorbing Zn < 2 + > and Cd < 2 + > is used as a photocatalytic adsorption material. Then polyvinylpyrrolidone, deionized water and thioacetamide are added to form a reaction solution containing a sulfur source, the reaction temperature and time are adjusted, thioacetamide is fully hydrolyzed under the condition, and CdS and ZnS deposits are formed on the surface of MOR after hydrothermal crystallization; and finally, adding g-C3N4 into an ethanol solution, carrying out ultrasonic treatment, mixing with ZnCdM, and carrying out self-assembly adsorption on the mixture on the surface through electrostatic attraction to prepare the g-C3N4 / CdS / ZnS (at) MOR composite photocatalytic material with high stability, high photocatalytic activity and excellent adsorption performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to photocatalytic materials, and specifically relates to a photocatalytic adsorption dual-functional material based on mordenite, and a preparation method and application thereof. Background Art

[0002] With the acceleration of industrialization, the emission of heavy metal pollutants has become increasingly serious, causing great harm to environmental factors such as soil and water sources. Heavy metals are toxic and difficult to degrade and be metabolized by the body in the natural environment. Their pollution has become a global environmental problem. Adsorption, as one of the common methods for removing heavy metal ions, has received widespread attention. Among many adsorbents, mordenite stands out due to its unique physical and chemical properties. It has the advantages of stable properties, strong weather resistance, large specific surface area and rich pore size. It has good adsorption performance and considerable reserves in nature. Artificially synthesized mordenite can also flexibly adjust the surface properties according to specific reaction conditions.

[0003] In addition, industries such as automobile manufacturing, metal smelting and mining will produce a large amount of Zn 2+ 、Contains Cd 2+ Wastewater not only wastes heavy metal resources, but also seriously threatens the surrounding ecological environment. Traditional treatment methods are difficult to effectively treat such wastewater, and recovering heavy metal ions in wastewater and converting them into materials with photocatalytic activity is a very promising solution. Traditional photocatalytic adsorbents have shown great potential in the fields of environmental governance and energy conversion, but they also have many shortcomings such as few surface active sites, insufficient adsorption capacity, poor stability and high cost. For example, CdS, as a commonly used photocatalytic material, has serious photocorrosion and high recombination rate of electron-hole pairs, which greatly limits its practical application effect.

[0004] In summary, the development of a new adsorption material that combines the advantages of materials such as mordenite and CdS is of great significance for improving water treatment efficiency, enhancing material stability, photocatalytic activity and solving environmental pollution problems. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a photocatalytic adsorption dual-functional material based on mordenite with high stability, high photocatalytic activity and excellent adsorption performance, as well as a preparation method and application thereof, to simultaneously realize the preparation of heavy metal ion recovery and high-efficiency photocatalytic synergistic adsorption materials for the concept of composite sustainable development in sewage treatment or soil remediation, and the preparation method is simple, low-cost, and can be used on a large scale.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0008] Step 1, dissolving sodium aluminate in deionized water, stirring evenly, adding sodium hydroxide and alkaline silica sol to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 180-185° C. for 90-96 hours, filtering the product, washing, drying, and placing it in a muffle furnace, heating it from room temperature to 540-550° C. and calcining it for 6-8 hours to obtain MOR;

[0009] The molar ratio of each substance in the MOR synthesis system is 2.1Na2O:Al2O3:16SiO2:320H2O;

[0010] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it from room temperature to 515-525°C, and calcine it for 4-6 hours to obtain g-C3N4;

[0011] Step 3: Dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR in a mass ratio of (20.4-20.8):(20.3-20.6):(49.5-50.2):(0.8-1.2) of zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1, soak for 2-2.5 hours and stir for 10-12 hours, collect the powder by centrifugation, and obtain the adsorbed Cd 2+ and Zn 2+ After drying, polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of (10-12): (0.14-0.16): (0.074-0.076): (0.198-0.210), and hydrothermally reacted at 178-185°C for 12-14h, filtered, and dried to obtain CdS / ZnS@MOR;

[0012] Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 1.5 to 2.5 hours. Add CdS / ZnS@MOR at a weight ratio of g-C3N4 to CdS / ZnS@MOR of (0.05 to 0.45):1 and stir for 3.5 to 4.5 hours. Collect the powder by centrifugation and dry it to obtain a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material.

[0013] The present invention also has the following technical features:

[0014] Preferably, the SiO2 content of the alkaline silica sol described in step 1 is 30wt%.

[0015] Furthermore, during the calcination process described in step 1 and step 2, the heating rate of the muffle furnace is 10° C. / min.

[0016] Furthermore, the drying in step 1, step 3 and step 4 is performed at 80° C. for 8 to 12 hours.

[0017] Preferably, the centrifugal speed in step three and step four is 5500 rpm.

[0018] Preferably, in step 4, the weight-to-volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL.

[0019] Preferably, the ultrasonic frequency described in step 4 is 30 kHz.

[0020] The present invention also protects a photocatalytic adsorption dual-functional material based on mordenite prepared by the method as described above and its application in heavy metal ion recovery and photocatalytic synergistic adsorption sewage treatment or soil remediation.

[0021] Compared with the prior art, the present invention has the following technical effects:

[0022] The present invention prepares mordenite MOR by a one-step hydrothermal crystallization process, and adds Zn-containing zeolite of different concentrations to the mordenite MOR. 2+ and Cd 2+ In aqueous solution, the electrostatic affinity and adsorption performance of mordenite are used to adsorb heavy metal ions in water, which can achieve the purpose of Zn 2+ and Cd 2+ The removal of heavy metals and the recycling of heavy metal resources are achieved at the same time, turning waste into treasure, which is in line with the concept of sustainable development. Subsequently, the mordenite adsorbed with heavy metal ions is dried and in-situ sulfurized to obtain CdS / ZnS@MOR (ZnCdM). As a carrier, the mordenite provides a stable and effective support for the active substance. Then, g-C3N4 is added to an ethanol solution and mixed with ZnCdM after ultrasonic treatment. The g-C3N4 / CdS / ZnS@MOR composite photocatalytic material is obtained by self-assembly and adsorption on its surface by electrostatic attraction. The porous structure of the mordenite has good adsorption capacity, and the MOR surface has smaller CdS nanoparticles, ZnS nanoparticles and g-C3N4 nanosheets. The smaller particle size not only increases the specific surface area of ​​the material, but also facilitates the exposure of active sites, thereby improving the photocatalytic activity.

[0023] The g-C3N4 / CdS / ZnS@MOR composite photocatalytic material prepared by the present invention has high photocatalytic activity for RhB under visible light, because mordenite as a carrier provides effective support for the active substance, the surface of the composite mordenite photocatalytic material has smaller CdS nanoparticles, ZnS nanoparticles and g-C3N4 nanosheets, which are easy to enrich RhB, and the electric field effect on MOR leads to a decrease in the recombination rate of photogenerated charges; in addition, the double Z charge transfer mechanism formed by the close contact between CdS, ZnS and g-C3N4 is conducive to charge separation, and this charge transfer mechanism can effectively inhibit the recombination of photogenerated electron-hole pairs, further improving the photocatalytic activity, and these combined effects improve the efficiency of photocatalytic degradation of Rhodamine B, and the process realizes a dual-functional material based on mordenite, and can realize a sustainable development strategy by converting harmful substances into practical materials, "turning waste into treasure", which is very beneficial to environmental protection;

[0024] The composite photocatalytic material of the present invention has good stability in photocatalytic performance in multiple cycle tests, which is due to the rigid skeleton structure of mordenite and the strong binding force between sulfide and mordenite. The rigid skeleton of mordenite can maintain structural stability under harsh conditions, and the strong binding force between sulfide and mordenite can prevent sulfide from falling off or being corroded during the reaction process, thereby ensuring the stability of the material.

[0025] The preparation method of the present invention simultaneously realizes the recovery of heavy metal ions and the preparation of high-efficiency photocatalytic synergistic adsorption materials. The prepared materials are used in sewage treatment or soil remediation to show high-efficiency adsorption performance and photocatalytic activity and can be recycled many times. At the same time, the preparation method is simple, low-cost, and can be used on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the synthesis of the g-C3N4 / CdS / ZnS@MOR composite photocatalytic material of the present invention;

[0027] Figure 2 The MOR prepared in Example 1 was subjected to 400 mg / L Zn at different times. 2+ and Cd 2+ Removal rate curve of mixed solution;

[0028] Figure 3 X-ray diffraction spectra of the products prepared in Examples 1 to 5;

[0029] Figure 4 Fourier infrared spectra of the products prepared in Examples 1 to 5 and Comparative Examples 1 and 2;

[0030] Figure 5The XPS spectra of the products prepared in Examples 1 to 5 and Comparative Examples 1 and 2 are shown;

[0031] Figure 6 The scanning electron microscope images of the products prepared in Example 1 and Comparative Example 1 and Comparative Example 2 are shown;

[0032] Figure 7 is the adsorption-desorption isotherm curve of the product prepared in Example 1;

[0033] Figure 8 The photocatalytic degradation RhB diagram of the products prepared in Examples 1 to 5 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0034] The specific contents of the present invention are further explained in detail in conjunction with the examples below. The synthesis schematic diagram of the g-C3N4 / CdS / ZnS@MOR composite photocatalytic material of the present invention is shown in Figure 1 As shown;

[0035] The concentration of the ethanol solution used in the following examples is 95%.

[0036] Example 1

[0037] This embodiment provides a method for preparing a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material, and the specific steps include:

[0038] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0039] Step 1, dissolving 1.075 parts of NaAlO2 in 6.683 parts of deionized water by mass, stirring for 15 minutes, adding 0.171 parts of NaOH to the solution and continuing to stir for 15 minutes, dropping 3.964 parts of alkaline silica sol with a SiO2 content of 30wt%, stirring for 120 minutes to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 180°C for 90 hours, filtering the product, washing it with deionized water for 3 times, drying it at 80°C for 8 hours, placing it in a muffle furnace and heating it to 550°C at a rate of 10°C / min and calcining it for 6 hours to obtain MOR;

[0040] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it to 520°C at a rate of 10°C / min, and calcine it for 4 hours to obtain g-C3N4;

[0041] Step 3: Take zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1 in a mass ratio of 20.4:20.3:49.5:0.8, dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR, soak for 2 hours and stir for 10 hours, collect powder by centrifugation at a speed of 5500 rpm, and obtain adsorbed Cd 2+ and Zn 2+ MOR was dried at 80°C for 8 hours, and then polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of 10:0.14:0.074:0.198, and hydrothermally reacted at 180°C for 13 hours, filtered, and dried at 80°C for 8 hours to obtain CdS / ZnS@MOR;

[0042] Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 1.5 hours. The weight volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL, the ultrasonic frequency is 30 kHz, and CdS / ZnS@MOR is added at a weight ratio of g-C3N4 to CdS / ZnS@MOR of 0.05:1 and stirred for 4 hours. The powder is collected by centrifugation at a centrifugal speed of 5500 rpm and dried at 80°C for 8 hours to obtain a composite photocatalytic material, represented by 5wt% g-C3N4 / CdS / ZnS@MOR.

[0043] Example 2

[0044] This embodiment provides a method for preparing a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material, and the specific steps include:

[0045] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0046] Step 1, dissolving 1.075 parts of NaAlO2 in 6.683 parts of deionized water by mass, stirring for 15 minutes, adding 0.171 parts of NaOH to the solution and continuing to stir for 15 minutes, dropping 3.964 parts of alkaline silica sol with a SiO2 content of 30wt%, stirring for 120 minutes to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 185°C for 92 hours, filtering the product, washing it with deionized water for 3 times, drying it at 80°C for 10 hours, placing it in a muffle furnace and heating it to 540°C at a rate of 10°C / min and calcining it for 7 hours to obtain MOR;

[0047] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it to 525°C at a rate of 10°C / min, and calcine it for 5 hours to obtain g-C3N4;

[0048] Step 3: Take zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1 in a mass ratio of 20.6:20.5:50:1, dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR, soak for 2.2 hours and stir for 11 hours, collect powder by centrifugation at a speed of 5500 rpm, and obtain adsorbed Cd 2+ and Zn 2+ MOR was dried at 80°C for 10 h, polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of 11:0.15:0.075:0.2, and hydrothermally reacted at 178°C for 12 h, filtered, and dried at 80°C for 10 h to obtain CdS / ZnS@MOR;

[0049] Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 2 hours. The weight volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL, the ultrasonic frequency is 30 kHz, and CdS / ZnS@MOR is added at a weight ratio of g-C3N4 to CdS / ZnS@MOR of 0.15:1, and stir for 3.5 hours. Collect the powder by centrifugation at a centrifugal speed of 5500 rpm, and dry at 80°C for 10 hours to obtain a composite photocatalytic material, expressed as 15wt% g-C3N4 / CdS / ZnS@MOR.

[0050] Example 3

[0051] This embodiment provides a method for preparing a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material, and the specific steps include:

[0052] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0053] Step 1, dissolving 1.075 parts of NaAlO2 in 6.683 parts of deionized water by mass, stirring for 15 minutes, adding 0.171 parts of NaOH to the solution and continuing to stir for 15 minutes, dropping 3.964 parts of alkaline silica sol with a SiO2 content of 30wt%, stirring for 120 minutes to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 182°C for 96 hours, filtering the product, washing it with deionized water for 3 times, drying it at 80°C for 12 hours, and then placing it in a muffle furnace and heating it to 545°C at a rate of 10°C / min and calcining it for 8 hours to obtain MOR;

[0054] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it to 515°C at a rate of 10°C / min, and calcine it for 6 hours to obtain g-C3N4;

[0055] Step 3: Take zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1 in a mass ratio of 20.8:20.6:50.2:1.2, dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR, soak for 2.2 hours and stir for 11 hours, collect powder by centrifugation at a speed of 5500 rpm, and obtain adsorbed Cd 2+ and Zn 2+ MOR was dried at 80°C for 12 h, and then polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of 12:0.15:0.076:0.210, and hydrothermally reacted at 185°C for 14 h, filtered, and dried at 80°C for 12 h to obtain CdS / ZnS@MOR;

[0056] Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 2.5 hours. The weight volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL, the ultrasonic frequency is 30 kHz, and CdS / ZnS@MOR is added at a weight ratio of g-C3N4 to CdS / ZnS@MOR of 0.25:1, and stir for 4.5 hours. Collect the powder by centrifugation at a centrifugal speed of 5500 rpm, and dry at 80°C for 12 hours to obtain a composite photocatalytic material, expressed as 25wt% g-C3N4 / CdS / ZnS@MOR.

[0057] Example 4

[0058] This embodiment provides a method for preparing a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material, and the specific steps include:

[0059] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0060] Step 1, dissolving 1.075 parts of NaAlO2 in 6.683 parts of deionized water by mass, stirring for 15 minutes, adding 0.171 parts of NaOH to the solution and continuing to stir for 15 minutes, dropping 3.964 parts of alkaline silica sol with a SiO2 content of 30wt%, stirring for 120 minutes to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 180°C for 96 hours, filtering the product, washing it with deionized water for 3 times, drying it at 80°C for 8 hours, and then placing it in a muffle furnace and heating it to 550°C at a rate of 10°C / min and calcining it for 6 hours to obtain MOR;

[0061] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it to 520°C at a rate of 10°C / min, and calcine it for 4 hours to obtain g-C3N4;

[0062] Step 3: Take zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1 in a mass ratio of 20.5:20.5:50:1, dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR, soak for 2.5 hours and stir for 12 hours, collect powder by centrifugation at a speed of 5500 rpm, and obtain adsorbed Cd 2+ and Zn 2+ MOR was dried at 80°C for 12 h, polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of 12:0.14:0.074:0.198, and hydrothermally reacted at 180°C for 13 h, filtered, and dried at 80°C for 12 h to obtain CdS / ZnS@MOR;

[0063] Step 4. Place g-C3N4 in an ethanol solution and ultrasonicate for 2 hours. The weight volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL, the ultrasonic frequency is 30 kHz, and CdS / ZnS@MOR is added at a weight ratio of g-C3N4 to CdS / ZnS@MOR of 0.35:1 and stirred for 4 hours. The powder is collected by centrifugation at a centrifugal speed of 5500 rpm and dried at 80°C for 12 hours to obtain a composite photocatalytic material, expressed as 35wt% g-C3N4 / CdS / ZnS@MOR.

[0064] Example 5

[0065] This embodiment provides a method for preparing a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material, and the specific steps include:

[0066] A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, comprising the following steps:

[0067] Step 1, dissolving 1.075 parts of NaAlO2 in 6.683 parts of deionized water by mass, stirring for 15 minutes, adding 0.171 parts of NaOH to the solution and continuing to stir for 15 minutes, dropping 3.964 parts of alkaline silica sol with a SiO2 content of 30wt%, stirring for 120 minutes to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 180°C for 96 hours, filtering the product, washing it with deionized water for 3 times, drying it at 80°C for 8 hours, and then placing it in a muffle furnace and heating it to 550°C at a rate of 10°C / min and calcining it for 6 hours to obtain MOR;

[0068] Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it to 520°C at a rate of 10°C / min, and calcine it for 4 hours to obtain g-C3N4;

[0069] Step 3: Take zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1 in a mass ratio of 20.5:20.5:50:1, dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR, soak for 2.2 hours and stir for 11 hours, collect powder by centrifugation at a speed of 5500 rpm, and obtain adsorbed Cd 2+ and Zn 2+ MOR was dried at 80°C for 12 h, polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of 12:0.14:0.074:0.198, and hydrothermally reacted at 180°C for 13 h, filtered, and dried at 80°C for 12 h to obtain CdS / ZnS@MOR;

[0070] Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 2 hours. The weight volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL, the ultrasonic frequency is 30 kHz, and CdS / ZnS@MOR is added at a weight ratio of g-C3N4 to CdS / ZnS@MOR of 0.45:1 and stirred for 4 hours. The powder is collected by centrifugation at a centrifugal speed of 5500 rpm and dried at 80°C for 12 hours to obtain a composite photocatalytic material, represented by 45wt% g-C3N4 / CdS / ZnS@MOR.

[0071] Comparative Example 1

[0072] CdS@MOR is prepared as a photocatalytic material. The synthesis steps of CdS@MOR include:

[0073] At 298K, 1g of mordenite was added to the solution containing different concentrations of heavy metal ions Cd 2+ After being immersed in 50 mL aqueous solution for 2.2 h and stirred for 11 h, the adsorbent was collected by high-speed centrifugation, and the collected powder was placed in an oven at 60 ° C and dried overnight for use. The product Cd 2+ / MOR; subsequently, 0.15 g of polyvinyl pyrrolidone was dissolved in 10 mL of deionized water, 1 mmol of thioacetamide was added and stirred evenly, 0.2 g of mordenite that adsorbs metal ions was added respectively, and the mixture was transferred into a reactor and subjected to hydrothermal reaction at 180 ° C for 13 hours. After standing and cooling to room temperature, the mixture was washed with deionized water for several times and dried to obtain the product CdS@MOR.

[0074] Comparative Example 2

[0075] ZnS@MOR is prepared as a photocatalytic material. The synthesis steps of ZnS@MOR include:

[0076] At 298K, 1g of mordenite was added to the solution containing different concentrations of heavy metal ions Zn 2+After being immersed in 50 mL of aqueous solution for 2.2 h and stirred for 11 h, the adsorbent was collected by high-speed centrifugation, and the collected powder was placed in an oven at 60 ° C and dried overnight for use. The product Zn 2+ / MOR; subsequently, 0.15 g of polyvinyl pyrrolidone was dissolved in 10 mL of deionized water, 1 mmol of thioacetamide was added and stirred evenly, 0.2 g of mordenite that adsorbs metal ions was added respectively, and the mixture was transferred into a reactor and subjected to hydrothermal reaction at 180 ° C for 13 hours. After standing and cooling to room temperature, the mixture was washed with deionized water for several times and dried to obtain the product ZnS@MOR.

[0077] Experimental Example 1

[0078] Adsorption characteristics of MOR zeolite for different metal ions

[0079] The MOR prepared in Example 1 reacted with 400 mg / L Zn at different times. 2+ and Cd 2+ The removal rate curve of the mixed solution is as follows: Figure 2 As shown in (a), MOR basically reaches adsorption equilibrium in about 4 hours. Different adsorption modes lead to slight differences in the time to reach equilibrium. 2+ and Cd 2+ The removal rates of Cd 2+ and Zn 2+ The concentrations were all 400 mg / L, and the removal rates of mordenite for them were 85.73% and 76.69%, respectively. The difference in removal rates was attributed to different adsorption modes. 2+ and Zn 2+ When coexisting, the removal rate of metal ions by mordenite decreases to a certain extent, but it still shows good adsorption performance. As the metal ion content in the aqueous solution increases, the removal rate begins to decrease. This is due to the competitive adsorption between metal ions. Therefore, 400 mg / L Cd 2+ and Zn 2+ As the adsorption solution of MOR zeolite. Different adsorption models such as Figure 2 (c) and the model parameters are shown in Table 2.

[0080] Table 1 The MOR prepared in Example 1 degraded Cd in solution within 4 hours 2+ or / and Zn 2+ Ion removal rate

[0081]

[0082] Table 2Cd 2+ and Zn 2+ Fitting parameters of adsorption Langmuir and Freundlich isotherm models

[0083]

[0084] Experimental Example 2

[0085] X-ray diffraction spectrum (XRD):

[0086] The different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 were characterized and compared with standard CdS, ZnS, and MOR. The obtained X-ray diffraction spectra are as follows: Figure 3 shown. Figure 3 (a) X-ray diffraction patterns of MOR, CdS / ZnS@MOR, 25wt% g-C3N4 / CdS / ZnS@MOR and (b) different materials after adjusting the weight ratio of g-C3N4 to CdS / ZnS@MOR.

[0087] Depend on Figure 3 (a) Observation shows that the modified materials all show characteristic diffraction peaks of MOR in the range of 5-60°, of which 9.75°, 22.21° and 25.58° belong to the (200), (150) and (202) crystal planes of mordenite, respectively, indicating that the skeleton of MOR has not changed after sulfurization. In addition, it can be seen from the figure that the characteristic diffraction peaks of CdS in the ZnCdM composite material correspond to the (100), (002) and (101) crystal planes, and the characteristic diffraction peak of CdS corresponds to the (111) crystal plane. The characteristic diffraction peak of g-C3N4 can be observed in ZnCdCM, and the diffraction peak corresponds to the (002) crystal plane. The XRD diffraction patterns of ZnCdCM with different g-C3N4 doping amounts are shown in Figure 1. Figure 3 As shown in (b), with the increase of g-C3N4 doping amount, the corresponding (002) crystal plane characteristic peak is enhanced, but the characteristic peak of MOR gradually decreases. This is caused by the decrease of MOR crystallinity due to the coating of g-C3N4.

[0088] Experimental Example 3

[0089] Fourier transform infrared spectroscopy (FT-IR):

[0090] The different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 were characterized and compared with CdS / MOR, ZnS / MOR and MOR. The Fourier transform infrared spectra obtained are as follows: Figure 4 shown. Figure 4 (b) Fourier infrared spectra of different materials after adjusting the weight ratio of g-C3N4 and CdS / ZnS@MOR.

[0091] from Figure 4The IR spectra of ZnM, CdM, ZnCdM and 25wt% ZnCdCM were observed at 810 cm -1 and 640cm -1 The 1225 cm-1 bands are respectively attributed to the symmetric stretching vibration of the MOR metal oxygen tetrahedron and the vibration of the framework oxygen ring channel. -1 Asymmetric stretching vibration outside the zeolite framework tetrahedron; 1634cm -1 It is attributed to Si-OH vibration. These are the infrared characteristic peaks of MOR zeolite. For the 25wt% ZnCdCM composite material, 1198cm -1 and 1645cm -1 Attributed to CN heterocyclic stretching mode vibration. 2790 to 3398 cm -1 The broad band between them is attributed to the -NH2 group. 3000cm -1 To 3510cm -1 Attributed to the stretching vibration of the defective aromatic ring. 2164cm -1 The asymmetric stretching vibrations corresponding to the cyano group (-CN or -NC) are the main characteristic peaks of g-C3N4. This proves that the structure of g-C3N4 in the 25wt% ZnCdCM composite prepared by ultrasonic treatment is not destroyed. In addition, the peaks at 1458 and 1150 cm -1 Characteristic peaks attributed to Zn-S: 1428, 1030 and 661 cm -1 All the main characteristic vibration peaks related to ZnS, CdS and g-C3N4 can be clearly found in the composite material, indicating that the 25wt% ZnCdCM composite material prepared by in-situ sulfurization and post-treatment of MOR molecular sieves adsorbing metal ions was successfully synthesized.

[0092] Experimental Example 4

[0093] XPS spectrum (XPS):

[0094] The different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 were characterized and compared with CdS@MOR, ZnS@MOR, and CdS / ZnS@MOR. The XPS spectra obtained are shown in Figure 5 shown. Figure 5 The XPS spectra of different composite photocatalytic materials are shown in Figure 2. Figure 5 (a) is the XPS full spectrum. Figure 5 (b), (c) and (d) are the detailed spectra of S2p. Figure 5 (e) and (f) are the fine spectra of Cd3d. Figure 5 (g) and (h) are the fine spectra of O1s; Figure 5(i) is the detailed spectrum of C1s and N1s.

[0095] exist Figure 5 In (a), we can observe the XPS measurement scan results of 25wt% ZnCdCM in a low-resolution and large energy range. Figure 5 (b) shows the peaks of Si, Zn, Cd, S, C and N in the 25wt% ZnCdCM composite. This indicates the successful preparation of the 25wt% ZnCdCM composite. The peaks of CdS at 405.3eV and 412.1eV correspond to Cd 3d 5 / 2 and Cd 3d 3 / 2 , the peaks at 161.3 eV and 162.6 eV are attributed to S2p 3 / 2 and S2p 1 / 2 The peaks of ZnS at 1022.8 eV correspond to Zn 2p 3 / 2 , the peaks at 161.8eV and 163.1eV are respectively attributed to S2p 3 / 2 and S2p 1 / 2 The peaks at 161.4 eV and 162.5 eV are attributed to S2p 3 / 2 and S2p 1 / 2 Compared with CdS and ZnS, the peaks of binding energies of Cd 3d, Zn2p, and S2p in 25wt% ZnCdCM shift to different positions. 3 / 2 and S2p 1 / 2 Moved to 161.6eV and 162.8eV respectively, Zn2p 3 / 2 Move to 1021.9eV, Cd 3d 5 / 2 and Cd 3d 3 / 2 The C1s peaks of g-C3N4 at 284.5 eV and 287.7 eV can be attributed to the sp2 bonded carbon (CC) and sp2 hybridized carbon (N–C=N) in the sample, respectively. The three characteristic peaks at 398.0 eV, 398.7 eV and 400.0 eV in the N1s XPS spectrum of g-C3N4 should belong to C–N=C species, N–(C)3 groups and C–N–H bonds, respectively. Compared with g-C3N4, the C1s peak and N1s in 25wt% ZnCdCM were slightly shifted. These shifts are caused by the changes in electron density generated at the interface due to the interaction between MOR and ZnS, CdS and g-C3N4, proving that there is a strong interaction between the nanoparticles and nanosheets and MOR molecular sieves in the prepared 25wt% ZnCdCM composite material, which will be beneficial to the separation of photogenerated carriers.

[0096] Experimental Example 5

[0097] Scanning electron microscope (SEM):

[0098] The morphology of the different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 was characterized and compared with CdS@MOR, ZnS@MOR, and CdS / ZnS@MOR. The SEM images obtained are as follows: Figure 6 shown.

[0099] Figure 6 Scanning electron microscope images of (a) CdS, (b, c) CdM, (d) ZnS, (e, f) ZnM at different magnifications, scanning electron microscope images of (g), (h), (i) ZnCdM at different magnifications, and (j) EDX element distribution map of ZnCdM.

[0100] In scanning electron microscopy Figure 6 As can be seen from (a, d), monomers of CdS and ZnS are agglomerated nanoparticles. These agglomerated nanoparticles reduce the specific surface area of ​​the catalyst, which is not conducive to the contact between the catalyst and the reactants, and reduces the catalytic efficiency. In addition, compared with uniformly dispersed nanoparticles, the photocatalytic activity of agglomerated CdS and ZnS nanoparticles is reduced. Figure 6 As can be seen in (b, e), MOR zeolite adsorbs Zn 2+ and Cd 2+ After sulfurization, CdS and ZnS nanoparticles grow on its surface. Figure 6 As can be seen in (b, c), the prepared CdM composite material has a layer of CdS nanoparticles uniformly grown on the surface of the disc-shaped MOR zeolite, and the size of these nanoparticles is about 80nm. Similarly, the ZnM composite material also grows ZnS nanoparticles on the surface of the disc-shaped MOR zeolite. After comparison, it can be seen that these CdS and ZnS grown on the surface of the MOR zeolite have smaller sizes than monomers CdS and ZnS. The results show that the adsorption of Cd by MOR zeolite 2+ and Zn 2+, and then the composite material prepared by sulfurization can better disperse CdS and ZnS nanoparticles and make them have a smaller particle size. In addition, CdM and ZnM still maintain the MOR disc structure, and evenly distributed CdS and ZnS nanoparticles can be seen on their surface, indicating that the structure of MOR is not destroyed during the synthesis process, proving that MOR zeolite has a certain stability as a carrier and adsorbent. It can be concluded that after the MOR zeolite adsorbs heavy metal ions and then undergoes in-situ sulfurization, the metal sulfide obtained has a smaller particle size and can effectively avoid agglomeration. In the photocatalytic reaction, smaller and evenly dispersed nanoparticles can provide a larger contact area with the reactants, increase the photocatalytic activity, and reduce the easy recombination of photogenerated carriers caused by agglomeration. Through the MOR adsorption of Cd 2+ and Zn 2+ , and then the composite material prepared by sulfurization can disperse CdS and ZnS nanoparticles with a smaller particle size. In addition, CdM and ZnM still maintain the MOR disc structure, and evenly distributed CdS and ZnS nanoparticles can be seen on their surface, which shows that the synthesis process did not destroy the structure of MOR, proving that MOR has a certain stability as a carrier and adsorbent. It is concluded that the metal sulfide obtained by MOR adsorbing heavy metal ions and then in-situ sulfurization has a smaller particle size and can effectively avoid agglomeration. In the photocatalytic reaction, smaller and evenly dispersed nanoparticles can provide a larger contact area with the reactants, increase the photocatalytic activity, and reduce the photogenerated carriers that are prone to composite phenomena due to agglomeration. Figure 6 (g, h, i) show the SEM images of ZnCdM. Two different sizes of nanoparticles can be seen on the MOR surface, corresponding to CdS and ZnS nanoparticles, which are in contact with each other. Figure 6 As shown in (j), the elements Zn, Cd, and S can be seen in the sample through EDS element mapping and are evenly distributed on the MOR surface, which indicates that CdS and ZnS are formed on the MOR surface, they are in close contact with each other, and form an interface that is conducive to carrier transport.

[0101] Experimental Example 6

[0102] Adsorption-desorption isotherms and pore size distribution characterization:

[0103] The morphology and pore structure of the different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5 were characterized and compared with CdS@MOR, ZnS@MOR, and CdS / ZnS@MOR. The adsorption-desorption isotherm curves obtained are shown in FIG. Figure 7 shown.

[0104] Figure 7 (ac) are adsorption-desorption isotherms.

[0105] Nitrogen adsorption and desorption isotherms of different samples are shown in Figure 2. Figure 7 As shown in Figure 2, MOR has typical micropore characteristics in the low specific pressure area, with a specific surface area of ​​373 m 2 g -1 , which is consistent with the literature, indicating a large specific surface area and an open pore structure. In addition, P / P0 increased significantly from 0.96 to 0.99, proving that the synthesized ZnCdM and 25wt% ZnCdCM composites have macroporous voids like MOR. Compared with the specific surface area and total pore volume of MOR, the ZnCdM and ZnCdCM composites have a certain degree of decrease, which is caused by the surface coverage of metal sulfides and carbonitrides, proving that there is an interface of mutual contact between the substances in the synthesized 25wt% ZnCdCM composite material, which is conducive to the transmission of electrons. ZnCdCM exhibits a type IV adsorption isotherm, which indicates the presence of a mesoporous structure with a specific surface area of ​​245m 2 g -1 , which is more conducive to the transport of reactants during the photocatalytic process.

[0106] Experimental Example 7

[0107] Photocatalytic degradation of RhB test:

[0108] The photocatalytic degradation of RhB was tested on the different g-C3N4 / CdS / ZnS@MOR composite photocatalytic materials obtained by the technical solutions of Examples 1 to 5. All samples were placed in a dark environment before the photocatalytic reaction to allow them to reach adsorption and desorption equilibrium for RhB. After the dark reaction for 1 hour, the synthesized samples were tested for photocatalytic degradation of RhB. The results are as follows Figure 8 shown.

[0109] Figure 8 (a) is the photocatalytic effect diagram of ZnCdCM with different g-C3N4 contents on RhB degradation under visible light and its kinetic constant (b), (c) is the photocatalytic effect diagram of different photocatalytic materials on RhB degradation under visible light and its kinetic constant (d).

[0110] like Figure 8As shown in (a), when different contents of g-C3N4 are introduced into ZnCdM, the photocatalytic activity of the composite material for RhB can be effectively enhanced, and the photocatalytic activity increases with the increase of g-C3N4 incorporation amount. When the g-C3N4 incorporation amount is 25wt%, the photocatalytic activity is the highest. This is because the introduced g-C3N4 can form charge transfer with ZnS and CdS in the system, inhibit the complexation of photogenerated carriers, and increase the amount of active substances in the system. An appropriate amount of g-C3N4 forms fine nanosheets on the surface of the composite material, which improves the catalytic activity. However, as the amount of g-C3N4 increases, it begins to aggregate together and form agglomerates, thereby reducing the specific surface area. The aggregated state has a higher complexation rate of photogenerated carriers, which is not conducive to the separation of carriers and reduces the catalytic activity. In addition, the increase in the amount introduced leads to a "shielding effect", which affects the light response of ZnS and CdS in the photocatalytic system and reduces the catalytic effect. As shown Figure 8 (d) shows that compared with ZnS (0.2767h -1 ) and CdS (0.4229h -1 ) compared to the ZnM introduced into MOR (0.3087h -1 ) and CdM(0.4874h -1 ) showed higher degradation efficiency, which was attributed to the fact that MOR could reduce the agglomeration of ZnS and CdS nanoparticles, which was beneficial to the exposure of photocatalytic active sites. In addition, the electric field environment of MOR was beneficial to the separation of photogenerated carriers. When CdS and ZnS existed on the surface of MOR in the form of a mixed phase, the rate constant of ZnCdM could reach 0.5040h -1 , indicating that ZnS and CdS have a synergistic catalytic effect on MOR, which jointly promotes the separation of photogenerated carriers. Figure 8 As shown in (b), when 25 wt% g-C3N4 was added into the system, the rate constant of photocatalytic degradation of RhB was 3.6858 h at 1.5 h. -1 , much higher than g-C3N4 (0.7291h -1 ) and ZnCdM(0.5040h -1 ).from Figure 8 (a, c) It can be seen that 25wt% ZnCdCM has the highest degradation rate (99.79%) and the fastest response rate. 25wt% ZnCdCM has a higher relative degradation activity and can quickly degrade the dye under visible light. This is attributed to the interaction between g-C3N4 and ZnS and CdS in the system, which forms an effective electron transport between them. In addition, ultrasonically treated g-C3N4 can form thin nanosheets on MOR, which is conducive to the exposure of more active sites, which is consistent with the previous SEM image results, and the above-mentioned polymerization effects all promote the photocatalytic degradation of RhB.

[0111] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a photocatalytic adsorption dual-functional material based on mordenite, characterized in that: The following steps are involved: Step 1, dissolving sodium aluminate in deionized water, stirring evenly, adding sodium hydroxide and alkaline silica sol to obtain a MOR synthesis system, crystallizing the MOR synthesis system at 180-185° C. for 90-96 hours, filtering the product, washing, drying, and placing it in a muffle furnace, heating it from room temperature to 540-550° C. and calcining it for 6-8 hours to obtain MOR; The molar ratio of each substance in the MOR synthesis system is 2.1Na2O:Al2O3:16SiO2:320H2O; Step 2: Place melamine in a crucible, wrap it with aluminum foil, place it in a furnace, heat it from room temperature to 515-525°C, and calcine it for 4-6 hours to obtain g-C3N4; Step 3: Dissolve zinc chloride and cadmium chloride in deionized water and mix with MOR in a mass ratio of (20.4-20.8):(20.3-20.6):(49.5-50.2):(0.8-1.2) of zinc chloride, cadmium chloride, deionized water and MOR prepared in step 1, soak for 2-2.5 hours and stir for 10-12 hours, collect the powder by centrifugation, and obtain the adsorbed Cd 2+ and Zn 2+ After drying, polyvinyl pyrrolidone, deionized water and thioacetamide were added according to the mass ratio of deionized water, polyvinyl pyrrolidone, thioacetamide and MOR of (10-12): (0.14-0.16): (0.074-0.076): (0.198-0.210), and hydrothermally reacted at 178-185°C for 12-14h, filtered, and dried to obtain CdS / ZnS@MOR; Step 4: Place g-C3N4 in an ethanol solution and ultrasonicate for 1.5 to 2.5 hours. Add CdS / ZnS@MOR at a weight ratio of g-C3N4 to CdS / ZnS@MOR of (0.05 to 0.45):1 and stir for 3.5 to 4.5 hours. Collect the powder by centrifugation and dry it to obtain a g-C3N4 / CdS / ZnS@MOR composite photocatalytic material.

2. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: The SiO2 content of the alkaline silica sol described in step 1 is 30wt%.

3. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: During the calcination process described in step 1 and step 2, the heating rate of the muffle furnace is 10° C. / min.

4. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: The drying in step 1, step 3 and step 4 is performed at 80° C. for 8 to 12 hours.

5. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: The centrifugal speed described in step 3 and step 4 is 5500 rpm.

6. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: In the step 4, the weight-to-volume ratio of g-C3N4 to ethanol solution is 1 g:8 mL.

7. The method for preparing the photocatalytic adsorption dual-functional material based on mordenite according to claim 1, characterized in that: The ultrasonic frequency described in step 4 is 30 kHz.

8. A photocatalytic adsorption dual-functional material based on mordenite prepared by the method according to any one of claims 1 to 7.

9. Use of the photocatalytic adsorption dual-functional material based on mordenite as claimed in claim 8 in heavy metal ion recovery and photocatalytic synergistic adsorption sewage treatment or soil remediation.